Effects of boron on the fracture behavior and ductility of cast Ti–6Al–4V alloys. (15th April 2015) - Luan, J.H.; Jiao, Z.B.; Heatherly, L.; George, E.P.; Chen, G.; Liu, C.T.
Abstract : Minor amounts of boron additions have been found to greatly enhance the ductility of cast Ti–6Al–4V alloys, which was considered to be due to the grain-size refinement. In this paper, we report our interesting finding that the beneficial effect of boron on the ductility of the cast titanium alloys is due not only to the grain-size refinement but the enhancement of the prior- β grain-boundary cohesion by boron segregation at the grain boundaries, as evidenced by Auger electron microscopy.